Intradural Disc Extrusion in a Dog - Ripplinger, Angel; Aiello, Graciane; Wrzesinski, Mathias Reginatto; Schwab, Marcelo Luís; Rauber, Júlia da Silva; Ferrarin, Dênis Antonio; Chaves, Julya Nathalya; Mazzanti, Alexandre (Acta Scientiae Veterinariae, 2020)
Background: Intervertebral disc extrusion is an important cause of spinal cord dysfunction in dogs. Intradural localization of the extruded disc material is rare, and is generally associated with a traumatic event or with recurrence of disc extrusion at a previously affected site. We report the clinical presentation, diagnostic workup, and treatment of a dog with intradural intervertebral disc extrusion not preceded by a traumatic event. Case: A 6-year-old male Dachshund was referred for neurological evaluation due to acute onset of hind-end paralysis preceded by claudication of the left hindlimb. The patient had been receiving conservative treatment to no effect. Neurological examination revealed asymmetric non-ambulatory paraparesis, absence of postural reactions and decreased muscle tone in both hindlimbs, a bilaterally diminished patellar reflex, and a hindlimb withdrawal reflex which was normal on the right and greatly diminished to absent on the left. The lower back was tender to epaxial palpation. Plain radiographs of the lumbar spine in the lateral projection showed calcified material within the spinal canal between the third and fourth lumbar vertebrae. Myelography was suggestively abnormal at the same level, with epidural leakage of contrast at L3-L4. Considering the clinical history, breed, age, neurological signs, and radiographic findings, intervertebral disc disease was suspected despite the inconclusive myelography findings. A dorsolateral lumbar hemilaminectomy was performed. Intraoperatively, the diagnosis was confirmed by visualization of a discolored spinal cord and absence of extradural material. The intradural space was accessed via durotomy. A firm, straw-yellow material was seen compressing the spinal cord and removed. Subsequent histopathological examination confirmed that this material consisted of extruded intervertebral disc contents. Postoperatively, the patient underwent physiotherapy and achieved a satisfactory recovery. Discussion: The most common cause of paraparesis in chondrodystrophic dog breeds is intervertebral disc extrusion. Intradural extrusion of the intervertebral disc is a rare phenomenon, often associated with vigorous exercise that causes laceration of the dura mater, allowing penetration of disc material into the intradural space. Although there were no classic signs of intervertebral disc disease on plain radiography, radiopaque material was visible within the spinal canal, which can occur in cases of calcified intervertebral disc extrusion. Myelography was inconclusive, but the decision was made to operate nevertheless, considering that the patient had not responded to conservative treatment and that surgical treatment is the most suitable approach for dogs with non-ambulatory paraparesis or paraplegia secondary to intervertebral disc extrusion. The surgical technique consisted of a hemilaminectomy and durotomy. Our diagnostic suspicion was confirmed intraoperatively, as in most cases of intradural disc extrusion in humans. Intradural disc extrusion is an uncommon phenomenon in dogs, and the diagnosis is usually only established intraoperatively. This unusual variant of intravertebral disc disease should be included in the differential diagnosis of spinal cord dysfunction in chondrodystrophic breeds, even in the absence of a history of trauma or preexisting intervertebral disc disease. Clinical treatment appears ineffective in these cases. Conversely, surgical treatment can yield good outcomes, and even functional recovery.